EFEKTIVITAS PENGAWASAN INSPEKTORAT TERHADAP PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN POLEWALI MANDAR - Andi Iskandar Sihab (Siddiq Institute, 2022)
This study focuses on the effectiveness of supervision in the implementation of the Polewali Mandar district government carried out by the Inspectorate Office of the Polewali Mandar district and then evaluates the effectiveness of supervision. As for the criteria for validating the data used in this study is the Triangulation Method, namely the use of various methods to examine a matter, such as the interview method and the observation method. In this study, the researcher conducted an interview method which was supported by the observation method at the time the interview was conducted.The process of data analysis is carried out continuously starting with examining all available data from various sources, namely from interviews, observations that have been written in field notes, documents and so on until conclusions are drawn. The effectiveness of supervising the implementation of local government is reviewed from the timeliness experienced by the follow-up team of the Polewali Mandar District Inspectorate who was not punctual in completing reports because in general there were many audit objects who were often late in presenting the findings data as requested by the follow-up team, and in In this regard, the Inspectorate follow-up team, in terms of the objectivity of the supervision carried out in general according to the object of supervision, is objective. In terms of the monitoring procedures carried out by the follow-up team, it has been running well and in accordance with established procedures. Meanwhile, the monitoring standards of the Inspectorate follow-up team are in accordance with the standards with reference to the supervision performance indicators stipulated in the inspectorate's rules and regulations in general. The factors that influence the effectiveness of the Inspectorate's supervision of Regional Finance management in Polewali Mandar district are the lack of auditors and in terms of accuracy the data is still incomplete, and has not been presented in actual terms. Several Work Units of the Regional Government of Polewali Mandar Regency were unable to present data according to findings and to be accountable for these findings to the Inspectorate follow-up team.